Upaya Meningkatkan Hasil Belajar Matematika Peserta Didik Pada Materi Statistika melalui Model Example Non Example Kelas XII IPS SMA Negeri 1 Singkep Tahun Ajaran 2021/2022 - Rislayanti Rislayanti (Ridwan Institute, 2022)
In the learning process to develop students' creativity, critical thinking skills are one of the important things, because with critical thinking students will use the potential of their minds to the fullest to solve a problem they face in everyday life. This type of research is a type of classroom action research conducted by the teacher as an effort to solve problems and improve the quality of learning in the classroom. The reason for using this type of research is because there are still many student scores that have not reached the limit of completeness so that researchers want to try to apply the Example Non Example learning model in this classroom action research. This research was carried out using an instrument of observing the activities of students in groups, and the test as an instrument that has been validated by the validator to determine learning outcomes using the Example Non Example learning model for students of class XII IPS 3 at SMA Negeri 1 Singkep. This activity was carried out in two cycles with five meetings, where there were two meetings in the first cycle and three meetings in the second cycle. The students' learning activities in the first cycle were presented classically reaching 79% and in the second cycle 87%, which means that in the implementation of the application of this model the results were good, an increase of 8%. As for the results of group assignments in working on the questions, all of them reached the KKM, which was 75 both in cycle I and cycle II. The classical average of the first cycle group was 83 and the second cycle was 89 increased. While the learning outcomes of students who completed the first cycle were 18 people with a percentage of 64%, while the second cycle students who completed were 25 people with a percentage of 89%, so the increase reached 25%.